Toxicity of ethylene oxide on the lens and on leukocytes: an epidemiological study in hospital sterilisation installations. Issue 5 (May 1990) - Deschamps, D; Leport, M; Laurent, A M; Cordier, S; Festy, B; Conso, F
Abstract : An epidemiological study was conducted in 55 subjects (mean age: 41) in hospitals to determine the prevalence of lens opacities and cataracts in workers exposed to ethylene oxide in six sterilisation units. The 21 exposed subjects over 45 were then compared with 16 non-exposed subjects, matched for age and sex. The relation between occupational exposure to ethylene oxide and white blood cell concentrations was also investigated. Lens opacities (independently of visual acuity) were observed in 19 of the 55 exposed. Among both exposed and non-exposed aged over 45, there were no significant differences with regard to the characteristics of lens opacities--prevalence (19 in the 21 exposed; 10 in the 16 non-exposed), distribution of the location, and importance and type (opalescence or discontinuous opacities). No link was found between the characteristics of the lens opacities and the characteristics of exposure: habitual exposure, measured between 0.06 and 39 ppm (cumulated in ppm-number of weekly hours-years) and accidental over-exposures (regular and irregular). For cataracts, defined by the association of lens opacities and a visual acuity less than 20/25 (this loss not being attributable to another cause), their prevalence differed significantly (p less than 0.05) between the exposed (six of 21) and the non-exposed (0 of 16); there was no relation between their existence and overexposures (the analysis for habitual exposure was not possible because of the small size of the sample). The risk of lens opacifications by ethylene oxide in cases of massive exposures as previously described could also exist during chronic exposure to low concentrations. It could be explained by saturation of protective mechanisms against alkylating action of this product. Linear relations were found between the logarithms of blood concentrations of polymorphoneutrophils (R=-0.54; p<0.005) and of lymphocytes (R=-0.45;p<0.05).